Structurally diverse dehydroshikimate dehydratase variants participate in microbial quinate catabolism. Issue 1 (3rd November 2016) - Peek, James; Roman, Joseph; Moran, Graham R.; Christendat, Dinesh
Summary: Quinate and shikimate can be degraded by a number of microbes. Dehydroshikimate dehydratases (DSDs) play a central role in this process, catalyzing the conversion of 3‐dehydroshikimate to protocatechuate, a common intermediate of aromatic degradation pathways. DSDs have applications in metabolic engineering for the production of valuable protocatechuate‐derived molecules. Although a number of Gram‐negative bacteria are known to catabolize quinate and shikimate, only limited information exists on the quinate/shikimate catabolic enzymes found in these organisms. Here, we have functionally and structurally characterized a putative DSD designated QuiC1, which is present in some pseudomonads. The QuiC1 protein is not related by sequence with previously identified DSDs from the Gram‐negative genus, Acinetobacter, but instead shows limited sequence identity in its N‐terminal half with fungal DSDs. Analysis of a Pseudomonas aeruginosa quiC1 gene knock‐out demonstrates that it is important for growth on either quinate or shikimate. The structure of a QuiC1 enzyme from P. putida reveals that the protein is a fusion of two distinct modules: an N‐terminal sugar phosphate isomerase‐like domain associated with DSD activity and a novel C‐terminal hydroxyphenylpyruvate dioxygenase‐like domain. The results of this study highlight the considerable diversity of enzymes that participate in quinate/shikimate catabolism in different microbes. Abstract : The Pseudomonas protein, QuiC1, is a novel dimeric 'two‐domain' dehydroshikimate dehydratase (DSD) that participates in the catabolism of quinate and shikimate. The Nterminal half of the protein is associated with DSD activity while an enigmatic Cterminal domain resembles hydroxyphenylpyruvate dioxygenase. At least four DSD subclasses can now be identified among bacteria and fungi, each with distinct structural properties.